Malaria control initiatives that have the potential to be gamechangers in India's quest for malaria elimination - Manju Rahi; Amit Sharma (Elsevier, 2022)
Summary: Malaria continues to have devastating effect on people's lives especially in developing countries. India is slated for malaria elimination by 2030. Though India has sustained a decline in malaria burden at the national level the epidemiological picture remains heterogenous. India's road to malaria elimination plan is riddled with many roadblocks. Major challenges include insufficient surveillance, slow and aggregated data reporting especially in exigent situations like cross-border areas and vulnerable high-risk groups. More than half of total malaria cases were due to Plasmodium vivax (P. vivax) in India as reported by national malaria control programme in 2019. This translates into substantial burden of P. vivax malaria in absolute numbers. P. vivax malaria, which is difficult to resolve as compared to other species, poses a threat to India's elimination plans by virtue of its tendency to develop hypnozoites, due to poor compliance to primaquine (PQ), due to host factors like G 6 PD deficiency and other genes that affect PQ metabolism. Also, India's malaria endemic areas largely coincide geographically with tribal regions which are poor in healthcare infrastructure. The tribal population disproportionately bears a huge burden of malaria. They also harbour more G6PD deficient individuals than non-tribal regions. Therefore, in addition to inadequate diagnostic facilities (for both malaria and G6PD testing) these remote rural and tribal communities suffer from lack of timely treatment, incomplete radical treatment due to poor compliance and thus repeated episodes of P. vivax due to relapses and/or reinfections. Another challenge is that the the current diagnostic tools in the national programme in India and other countries are mostly available only via the programme and are able to detect patent infections on the whole. These therefore miss low-density infections which are another major limitation for their use in malaria endemic countries. Drug and insecticide resistance need to be constantly monitored as they have direct impact on the efficacy of the current tools. Need for better vector control products for the diverse entomological requirements is also felt. India is the second most populous country in the world with majority of its population at risk of malaria. Despite many agencies (government and non-government) working in the field of malaria, there needs to be more synergy at the local or central level for malaria control. Here, we have proposed solutions for specific facets of the malaria programme. Surveillance, data visualization and analysis can all be supported through over the counter availability of rapid diagnostics, adoption of molecular tools like PCR (requiring additional infrastructure and expertise), mobile applications for data capture and use of malaria data dashboard. Management could be augmented by inclusion of tafenoquine for treatment of P. vivax malaria with a companion point-of care diagnostic which has been developed to assess G6PD enzyme activity. A switchover to artemether-lumefantrine for the entire country can also be considered. Vector control can be strengthened by commercial availability of insecticidal bednets and exploration of novel vector control tools like ivermectin. Lastly, enhancing synergy amongst various stakeholders would also catalyze the malaria elimination plans. Funding: The authors have received no funding for this paper.